Micronuclei test application to wild tropical ichthyic species common in two lentic environments of the low zones in Colombia (2009)
ABSTRACT: The presence of genotoxic stress in eight ichthyic species in two tropical lentic environments of Colombia [cachimbero (Santander) and Ayapel (Cordoba) floodplains lakes] was evaluated by the micronuclei test. After capturing and identifying each specimen, morphometric measurements were taken, and a blood sample drawn through cardiac or caudal vein puncture. Blood smears were stained with Giemsa and the frequency of micronuclei was quantified in 2000 cells per individual. A total of 11 species, 128 individuals, and 256.000 erythrocytes were evaluated. the condition factor for each captured specimen was calculated and a K-W analysis was applied in order to compare the number of MN among the different species in each lentic systems. The results showed a statistically significant relation between the condition factor and the frequency of micronucleated erythrocytes for the Ayapel floodplain lake. The less human-intervened floodplain lake (Cachimbero) showed the highest number of specimens with zero micronucleus, being Hoplias malabaricus the most sensitive species. The contrary occurs in the Ayapel floodplain lake contaminated with alluvial gold mining residues, where Ctenolucius sujeta and the native Cyphocharax magdalenae species presented the highest micronuclei averages. Our results further suggest that both sensitive and non-sensitive species should be included as sentinels in biomonitoring studies in Colombia.